2016
DOI: 10.1007/s10865-016-9742-x
|View full text |Cite
|
Sign up to set email alerts
|

Linking childhood abuse and hypertension: sleep disturbance and inflammation as mediators

Abstract: The indirect association of childhood abuse with prevalent hypertension in adulthood through sleep disturbance and pro-inflammatory biomarkers was investigated in 589 community-dwelling, middle-aged adults. Participants completed the Childhood Trauma Questionnaire and self-reported current sleep disturbance and medical diagnoses including hypertension. Blood pressure was taken and blood samples were analyzed for C-reactive protein, interleukin-6, and fibrinogen. Hypertension was present in 41.3% of the sample.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 47 publications
2
26
0
Order By: Relevance
“…It is generally believed that CSA is associated with elevated levels of circulating inflammatory biomarkers. [12][13][14][15][16][17][18] The present study reveals a negative…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…It is generally believed that CSA is associated with elevated levels of circulating inflammatory biomarkers. [12][13][14][15][16][17][18] The present study reveals a negative…”
Section: Discussionsupporting
confidence: 54%
“…[11] There is compelling evidence that childhood trauma is associated with elevated levels of circulating Interleukin inflammatory biomarkers several decades later, such as -6 (IL-6) and Interleukin-1β (IL-1β). [12][13][14][15][16][17][18] The association between CSA and inflammatory biomarkers remains unclear due to a significant amount of heterogeneity in the measures and methods employed in the literature. [19][20][21][22][23] Subgroup analyses undertaken in a recent meta-analysis study demonstrate only a weak association between CSA and adulthood IL-6 level.…”
Section: Introductionmentioning
confidence: 99%
“…Direct and indirect human and animal stress research supports the important supraordinate role of CS on stress system and GCs, linking circadian misalignment in ELS/CT-related pathophysiology and potentially resulting in the extensive comorbidities of ELS/CT through an impaired homeostatic balance. Some animal (332), but-most importantly-numerous human studies including large cohorts, have repeatedly confirmed that ELS/CT is independently associated with enduring adult sleep disruption including global sleep pathology (i.e., insomnia), as well as specific types of sleep problems, such as shortened total sleep time, prolonged sleep onset latency, decreased sleep efficiency, increased number of awakenings, nightmare related distress, sleep apnea and higher nocturnal activity in a probably dose-response manner (333)(334)(335)(336)(337)(338)(339)(340)(341)(342)(343)(344).…”
Section: Sleep and Circadian Systemmentioning
confidence: 97%
“…Evidence suggests that childhood maltreatment is associated with inflammation [47][48][49] and that inflammation mediates the association between childhood abuse and hypertension. 50 In women, inflammation explained more of the indirect effect than smoking. Although CRP is not causally related to CVD, 51 its production is stimulated by IL-6, which likely has a causal effect on CVD.…”
Section: Discussionmentioning
confidence: 99%